Age Stratification of 30-Day Postoperative Outcomes Following Excisional Laminectomy for Extradural Cervical and Thoracic Tumors. Issue 5 (August 2018) - Phan, Kevin; Cheung, Zoe B.; Vig, Khushdeep S.; Hussain, Awais K.; Lima, Mauricio C.; Kim, Jun S.; Di Capua, John; Cho, Samuel K.
Study Design: Retrospective cohort study. Objectives: To evaluate age as an independent predictive factor for perioperative morbidity and mortality in patients undergoing surgical decompression for metastatic cervical and thoracic spinal tumors using the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) database from 2011 to 2014. Methods: We identified 1673 adult patients undergoing excisional laminectomy of cervical and thoracic extradural tumors. Patients were stratified into quartiles based on age, with Q1 including patients aged 18 to 49 years, Q2 including patients aged 50 to 60 years, Q3 including patients aged 61 to 69 years, and Q4 including patients ≥70 years. Univariate and multivariate regression analyses were performed to examine the association between age and 30-day perioperative morbidity and mortality. Results: Age was an independent risk factor for 30-day venous thromboembolism (VTE) and reoperation. Patients in Q3 for age had nearly a 4 times increased risk of VTE than patients in Q1 (odds ratio [OR] 3.97; 95% CI 1.91-8.25; P < .001). However, there was no significant difference in VTE between patients in Q4 and Q1 ( P = .069). Patients in Q2 (OR 1.99; 95% CI 1.06-3.74; P = .032) and Q4 (OR 2.18; 95% CI 1.06-4.52; P = .036) for age had a 2 times increased risk of reoperation compared with patients in Q1. Conclusions: Age was an independent predictive factor for perioperative VTE and reoperation, but there was no clear age-dependent relationship between increasing age and the risk of these perioperative complications.